2004
DOI: 10.1007/s11159-004-4617-8
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of User-fee Policy on Attendance Rates among Kenyan Elementary Schoolchildren

Abstract: What happens when a government cannot meet its obligation to provide universal primary education and enhance the quality of education for all of its citizens? The present study examines the interactions among stakeholders in the user-fee policy in primary education in Kenya. It seeks to show how this policy has affected attendance rates and drop-out rates among elementary schoolchildren. It reveals that, in addition to limiting access and contributing to attrition, user-fees significantly contribute to absente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 11 publications
(16 reference statements)
0
8
0
Order By: Relevance
“…Over the years the Kenyan government has struggled to meet the challenges of expanding access to primary education and improving access to secondary education. Sporadic exceptional gains in enrolment have often been undermined by constraints in public and private financing (Mukudi 2004). The history of primary education in Kenya has been punctuated by a series of presidential decrees proclaiming the elimination of fees for schooling, which are later reintroduced through the back door.…”
Section: Perspectives On the Education Of Womenmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the years the Kenyan government has struggled to meet the challenges of expanding access to primary education and improving access to secondary education. Sporadic exceptional gains in enrolment have often been undermined by constraints in public and private financing (Mukudi 2004). The history of primary education in Kenya has been punctuated by a series of presidential decrees proclaiming the elimination of fees for schooling, which are later reintroduced through the back door.…”
Section: Perspectives On the Education Of Womenmentioning
confidence: 99%
“…The history of primary education in Kenya has been punctuated by a series of presidential decrees proclaiming the elimination of fees for schooling, which are later reintroduced through the back door. As an indicator of the extent of exclusion, a surge in enrolment always follows proclamations of free education, whereas a decline in participation inevitably occurs once the public begins to feel the pinch of new fees (Amutabi 2003;Eisemon and Schwille 1991;Mukudi 2004;Sifuna 2005Sifuna , 2007. Government and development agency interventions continue to focus on access to basic education, even though such an investment's potential for economic empowerment and according women social space in their communities is limited.…”
Section: Perspectives On the Education Of Womenmentioning
confidence: 99%
“…The cost of primary school figured prominently as a determinant for dropout and absenteeism. Enforcement of fee policies leads to long absences, occasionally resulting in dropout [ 48 ]. Therefore, reducing the primary school costs may improve the issues of dropout and absenteeism.…”
Section: Discussionmentioning
confidence: 99%
“…Amongst numerous factors, research has identified in whether children enrol in and attend school, direct and indirect schooling costs featured prominently (for example, Dachi & Garret, 2003:16;Fentiman, Hall & Bundy, 1999;Rose & Al Samarrai, 2001). Hunter (2008:09) maintains that while research on this often relates to access per se, there is also some research which indicates that the costs of schooling, including fees, is a central reason for dropping out (Brock & Cammish, 1997:27;Brown & Park, 2002;Colclough, Rose & Tembon, 2000;Hunter & May, 2003;Liu, 2004;May et al, 1998cited in Hunter & May, 2003Mukudi, 2004;Rose & Al Samarrai, 2001).…”
Section: School Fees and Associated Costs Of Schoolingmentioning
confidence: 99%
“…Not only do school fees lead to under-enrolment and drop out, they also limit attendance at school (Mukudi, 2004) and lead to temporary withdrawals. Research indicates children may be locked out of schools if they cannot pay schooling fees (Obasi, 2000;Ackers et al, 2001cited in Mukudi, 2004.…”
Section: School Fees and Associated Costs Of Schoolingmentioning
confidence: 99%